Viscosity and Interfacial Tension of Ternary Mixtures Consisting of Linear Alkanes, Alcohols, and/or Dissolved Gases Using Surface Light Scattering and Equilibrium Molecular Dynamics Simulations - Lenahan, Frances; Zhai, Ziwen; Hewa Kankanamge, Chathura Jayan Kankanamge; Klein, Tobias; Fröba, Andreas Paul (International Journal of Thermophysics, 2022)
Ternary mixtures consisting of liquids and dissolved gases with either two solvents or solutes are characterized by determining their liquid dynamic viscosity eta(L) and interfacial tension sigma using surface light scattering (SLS) and equilibrium molecular dynamics (EMD) simulations in the temperature range between (298 and 573) K and for mole fractions of the dissolved gas up to 0.20. The four ternary mixtures of interest are n-hexadecane + n-octacosane + carbon dioxide (CO2), n-hexadecane + nitrogen (N-2) + CO2, as well as 1-hexadecanol + n-octacosane with CO2 or water (H2O). With SLS, eta(L) and sigma of the two ternary mixtures containing n-hexadecane are accessed with average relative expanded experimental uncertainties (coverage factor k = 2) of u(r)(eta(L)) = 0.021 and u(r)(sigma) = 0.019. EMD simulations are performed for all four ternary mixtures and give access to eta(L) and sigma with average relative expanded statistical uncertainties (k = 2) of u(r)(eta(L)) = 0.15 and u(r)(sigma) = 0.061. The influence of the dissolved gases is investigated by comparing the thermophysical properties of the ternary mixtures to those of the pure solvent or the binary subsystems. The results for the ternary mixture consisting of n-hexadecane, n-octacosane, and CO2, which include a variation of the composition of the binary subsystem, i.e. the solvent mixture, have shown the reduction of both properties, due to dissolving CO2, to be independent of the solvent composition. For the ternary mixture consisting of n-hexadecane, N-2, and CO2, the reduction in both properties can be estimated by adding up the reduction determined for the binary subsystems, i.e. n-hexadecane with dissolved N-2 or CO2, which suggest that the presence of a further solute does not influence the impact of a dissolved gas.
Keywords: Gases; Hydrocarbons; Interfacial tension; Molecular dynamics simulations; Surface light scattering; Ternary mixtures; Viscosity